Influencing Generation Z’s Green Purchase Intention: Roles of Awareness and Eco-Labels - Utami Nur Illahi; Dewi Komala Sari; Rita Ambarwati; Mashhura Toirxonovna Alimova (LPPM Universitas PGRI Sumatera Barat, 2024)
Increasing population growth accompanied by excessive consumptive patterns encourages the exploitation of natural resources which will result in environmental pollution. Environmental problems that are not immediately resolved will certainly have an impact on the lives of the next generation. This study aims to determine the role of environmental awareness, consumption value and eco-labeling on green purchase intention in Generation Z. The theory used is the theory of consumption value initiated by Sheth et al. (1991) on how the nature of the customer decision-making process is based on 5 perceived consumption values, namely functional value, social value, emotional value, epistemic value and conditional value. The research method used is quantitative method with 135 respondents. Data analysis in this study used PLS-SEM analysis with the help of SmartPLS 3.0 software. The results showed that environmental awareness, consumption value and eco-label have a positive and significant effect on green purchase intention in Generation Z. The consumption value variable is the variable with the greatest influence on green purchase intention in Generation Z. The novelty of this research is the addition of consumption value variables using five dimensions of consumption value in accordance with the Theory of Consumption Values which are very rarely studied by Indonesian researchers in their influence on green purchase intention in generation Z.